Cooking Experience di Ubud: Keterlibatan Masyarakat Dalam Pariwisata Gastronomi - Wulandari, Pande Putu; Tirtawati, Ni Made; Dwi Candra Anggara, I Gusti Made (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Cooking experience, which is full of interactive and inclusive cultural activities between locals (host) and tourists (guest), is one of the gastronomic tourism activities in Ubud. Four key informants, namely cooking experience owners in the Ubud area and beyond, were involved in this research through interviews and observations. Desk research was also carried out to display comprehensive data. Through a qualitative descriptive approach, this article concludes that the existence of cooking experiences with various unique features ranging from the concept of cooking at home to